Evaluación de riesgo ergonómico del personal operativo del gad municipal san Cristóbal de Patate. - Pico Lasluisa, Oscar Omar (2019)
The main objective of the present research project is based on the ergonomic conditions analysis and it has as aims to evaluate the risks which are present in the operative staff in San Cristóbal de Patate municipality hall, regarding problems due to repetitive positions, forced positions and manual handling of charges; All these problems can be grouped as an ergonomic risk which is important to evaluate in order to protect the health and comfort of staff, as well as to increase the productivity in the organization. The work of all operational staff has been evaluated through the use of three evaluation methods: Risk Matrix Gtc 45 used to identify real risks which are being considered as serious, Rula which assesses the levels of ergonomic risk generated by the positions taken at the time of performing the tasks and Niosh which assesses the levels of ergonomic risk generated by the manual handling of loads. Once the elements have been evaluated, the results of the Rula method show that 46% of the operative staff has a serious level of ergonomic risk generated by the positions in which they develop their activities, so corrective measures must be taken immediately. Finally, the Niosh method determines that the manual handling of loads carried out by the operating staff in a 14% has a serious level, so that its intervention is necessary. Based on these results, it was determined that workers in the operational area perform their activities with inadequate postures, repetitive movements and excessive burdens, evidencing high levels of risk that expose workers from the operational area to suffer health conditions problems, so a corrective action plan to mitigate the ergonomic risks present in that area and to provide workers with the necessary information to prevent health problems was designed.